The role of host plants, land cover and bioclimate in predicting the invasiveness of Aromia bungii on a global scale - Enrico Ruzzier; Seunghyun Lee; Pietro Tirozzi; Valerio Orioli; Andrea Di Giulio; Olivia Dondina; Luciano Bani (Scientific Reports)
Abstract Aromia bungii is an invasive Cerambycidae of major concern at the global scale because of the damage caused to Rosaceae. Given the major phytosanitary relevance of A. bungii, predicting its spread in invaded areas and identifying possible new suitable regions worldwide remains a key action to develop appropriate management practices and optimise monitoring and early detection campaigns. To improve the predictive power of the modelling framework, a habitat suitability model (HSM), which includes host plants, was combined with a bioclimatic suitability model (BSM), both of which were calibrated on native occurrences. The range of A. bungii was substantially limited by the bioclimate, while habitat conditions acted as limiting factors in the species’ distribution. Host plants were the most important variable that positively influenced habitat suitability. Bioclimatic suitability improved as rainfall in the warmest quarter and average temperatures in the wettest quarter increased and as isothermality decreased. According to the combination of HSM and BSM, Japan is the most suitable area outside the native range of the species. In Europe, despite its high habitat suitability, it is difficult to expect a species to expand its range except through a substantial change in its bioclimatic niche.